Breastfeeding knowledge, attitude, and practices among mothers at EPI centers in the Northern part of Dhaka city - Afroz, Hasina; Mondal, Supta; Khatun, Taslima; Saleh, Farzana; Hussain, Md. Anower (The North African Journal of Food and Nutrition Research, 2024)
Background: Breastfeeding (BF) is crucial for newborns, providing immunization and strengthening the mother-infant bond. A study on breastfeeding knowledge, attitudes, and practices (KAP) at Expanded Program on Immunization (EPI) centers in our country is the first of its kind. Aims: This study aimed to assess the KAP regarding BF among mothers visiting EPI centers Subjects and Methods: This descriptive cross-sectional study was conducted among 400 mother-child pairs from June to December 2021 using purposive sampling. We used a semi-structured questionnaire from the Food and Agriculture Organization (FAO). We performed chi-squared tests and binary logistic regression analyses. Results: Approximately 63%, 65%, and 69% of mothers demonstrated satisfactory knowledge, attitudes, and practices towards BF, respectively. Mothers’ education level (p=0.0001), economic status (p=0.0001), and habitat (p=0.001) showed a significant relationship with their knowledge about BF. Of the participants, 85% received education on BF before delivery (p=0.0001), and 98% received it after delivery (p=0.03), both showing significant associations with good knowledge of BF. We observed a significant association (p=0.008) between economic status and mothers’ attitudes toward breastfeeding. Among the sociodemographic variables examined, only the mother’s age demonstrated a significant role (p=0.009) in breastfeeding practices, with about 38% of mothers aged over 25 exhibiting good breastfeeding practices. Using binary logistic regression analysis, mothers’ education, older age, monthly income, and education on BF during pregnancy and after delivery showed a significant (p≤0.05) association with KAP on BF. Conclusion: Knowledge, attitudes, and practices towards breastfeeding among mothers in the EPI centers were satisfactory. Education, older age, monthly income, and receiving education on breastfeeding during and after pregnancy were found to be determinants of satisfactory knowledge, attitudes, and practices. Keywords: Breastfeeding, Knowledge, Attitude, Practice, EPI center, Bangladesh